Peningkatan Usaha Lebah Klanceng Sebagai Ekonomi Alternatif Masyarakat Desa Tanggulangin Punggur Lamteng - Astuti, Hikmah Dwi; Laksmi, Dyah Ayu Vijaya (Lembaga Penelitian Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2022)
Klanceng bee cultivation is an opportunity for rural communities who have biological resources as an alternative economy. This Community Service was carried out in Tanggulangin Village, Punggur District, Central Lampung Regency. This activity takes place from January to March 2022. The aim is to help business development and marketing of klanceng honey. The main problems experienced by klanceng bee farmers are (1) it is difficult to market their harvested klang honey because the price is higher than other honey, (2) the klanceng honey bee farmer group has not yet been formed, (3) the absence of packaging registered with BPOM. The method used is the method of discussion, mentoring, and training. The results of the activity are in the form of planting bridal tear flower seeds, euphorbia flowers and mango tree seeds, creating an account at the e-commerce online store to reach a wider marketing of klanceng honey products. The packaging technique at the time of the training was still using ordinary plastic bottles which were less attractive and there were no brands registered with BPOM, so the PKM team assisted in making packaging brands and registering products with BPOM. With this PKM activity, it is hoped that the klanceng bee farmers will be able to manage their business so that they can become an alternative economic source and improve welfare.